A method for including a-priori preferences in multicriteria optimization - Heike Trautmann; Jörn Mehnen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
In this paper a method for including a-priori preferences of the decision makers into Multicriteria Optimization (MCO) problems is presented. A set of Pareto-optimal solutions is determined via desirability functions of the objectives which reveal experts preferences regarding different objective regions. By applying the method to the Binh-problem it proofs to be very effective for focusing on different parts of the Pareto front respectively the objective space of the original problem.
Keywords: 519